2006
DOI: 10.1124/dmd.105.007591
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal Growth Factor-Mediated Activation of the Map Kinase Cascade Results in Altered Expression and Function of Abcg2 (Bcrp)

Abstract: ABSTRACT:Epidermal growth factor (EGF) is a multifunctional growth factor known to play a major role in proliferation and differentiation processes. EGF-induced differentiation is a prerequisite for function of various cell types, among them cytotrophoblasts, a functionally important cellular fraction in human placenta. Stimulation of cytotrophoblasts with EGF results in formation of a multinuclear syncytium representing the feto-maternal interface, which protects the fetus against exogenous substances. It is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
92
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(103 citation statements)
references
References 40 publications
9
92
2
Order By: Relevance
“…HER2/HER3 signalling may also have a role in modulating the SP mainly through AKT ( Figure 4E). Although previous studies have reported an increase in SP cells by activation of HER1/EGFR signalling (Chen et al, 2006), and a stimulatory effect of EGF on BCRP gene transcription (Meyer zu Schwabedissen et al, 2006), experiments conducted by us comparing the effects of the HER2 inhibitor AG825 with that of the HER1 inhibitor AG1478 (Figure 4 and Supplementary Figure S4) demonstrate a predominant role of HER2/HER3 signalling over HER1 signalling in regulating the SP. HER1 inhibition and, thus, cessation of MAPK signalling could not reduce BCRP expression in GCC-BC4 cells despite inhibition of phospho p38 MAPK (Supplementary Figure S4B).…”
Section: Her2 Inhibitors Can Reduce the Sp And Prevent The Engraftmenmentioning
confidence: 99%
See 1 more Smart Citation
“…HER2/HER3 signalling may also have a role in modulating the SP mainly through AKT ( Figure 4E). Although previous studies have reported an increase in SP cells by activation of HER1/EGFR signalling (Chen et al, 2006), and a stimulatory effect of EGF on BCRP gene transcription (Meyer zu Schwabedissen et al, 2006), experiments conducted by us comparing the effects of the HER2 inhibitor AG825 with that of the HER1 inhibitor AG1478 (Figure 4 and Supplementary Figure S4) demonstrate a predominant role of HER2/HER3 signalling over HER1 signalling in regulating the SP. HER1 inhibition and, thus, cessation of MAPK signalling could not reduce BCRP expression in GCC-BC4 cells despite inhibition of phospho p38 MAPK (Supplementary Figure S4B).…”
Section: Her2 Inhibitors Can Reduce the Sp And Prevent The Engraftmenmentioning
confidence: 99%
“…Furthermore, the stimulatory effect of EGF on BCRP gene transcription has been reported in human breast (Meyer zu Schwabedissen et al, 2006) and ovarian cancer (Nakanishi et al, 2006b). Hence, we investigated whether HER2 could be a key regulatory factor for T-ICs found in the SP of BC.…”
mentioning
confidence: 99%
“…During trophoblast differentiation and syncytialization, BCRP and MRP1 expression is significantly increased, whereas MDR1 and MDR3 expression is markedly reduced (Pascolo et al, 2003;Evseenko et al, 2006a;Zu Schwabedissen et al, 2006); it is not known, however, whether this change in ABC expression profile is a function of differentiation or whether it plays an integral part of the differentiation process. Epidermal growth factor (EGF), which pro-motes in vitro trophoblast differentiation and protection from apoptosis (Morrish et al, 1998), increases BCRP expression in primary trophoblasts (Zu Schwabedissen et al, 2006), consistent with the increase in BCRP expression associated with syncytialization. Insulinlike growth factor II (IGF-II) is also known to be a major modulator of placental growth and development (Constancia et al, 2002) and is likely to be involved in regulation of apoptosis and cell differentiation.…”
mentioning
confidence: 94%
“…There is some evidence that their expression changes with gestational age, although the data are inconsistent (Patel et al, 2003;Mathias et al, 2005;Zu Schwabedissen et al, 2006). During trophoblast differentiation and syncytialization, BCRP and MRP1 expression is significantly increased, whereas MDR1 and MDR3 expression is markedly reduced (Pascolo et al, 2003;Evseenko et al, 2006a;Zu Schwabedissen et al, 2006); it is not known, however, whether this change in ABC expression profile is a function of differentiation or whether it plays an integral part of the differentiation process. Epidermal growth factor (EGF), which pro-motes in vitro trophoblast differentiation and protection from apoptosis (Morrish et al, 1998), increases BCRP expression in primary trophoblasts (Zu Schwabedissen et al, 2006), consistent with the increase in BCRP expression associated with syncytialization.…”
mentioning
confidence: 98%
“…56,59,60,91,94,178 Furthermore, EGF, functioning as a gastrointestinal mucosal protective factor attenuates hydrogen peroxideinduced disruption of tight junctions and barrier dysfunction. 94,123 EGF is known to activate ERK1/2 [179][180][181] via MAPK-ERK signaling pathway by activation of GRP, Ras and Raf and MEK. 182,183 It has been shown to prevent hydrogen peroxide-induced barrier disruption by an ERK-dependent mechanism in Caco-2 cells.…”
Section: Erk Mediates the Contrasting Effects Of Egf On Tight Junctiomentioning
confidence: 99%